Mechanical Properties of Composite Material Using Natural Rubber with Epoxy Resin - Hani Aziz Ameen (Engineering and Technology Journal, 2008)
In this paper the mechanical properties of three types of composite materials usingnatural rubber vulcanized, unvulcanized and reinforced rubber have beeninvestigated . The composite material using natural rubber and epoxy resin ismanufactured by three methods, first method is mixing the natural rubber withepoxy resin by special mixer without any additional materials, the second methodis to make a layer of rubber then coating it with a layer of epoxy resin and bondingusing the rolling process. The third one is use in the natural rubber as a matrixmaterial and using additional materials like carbon black in specific ratio and mixwith them the epoxy resin in five ratios ( 20%, 40%, 60%, 80%, and 100%) .The first and second methods failed because composite material produced wasinhomogeneous while the third method succeeded and the composite material washomogenous. Compression and hardness tests have been done on the resultingcomposite material of the third method and from the result it is found that thecomposite material has good properties and these properties improved byincreasing the ratio of epoxy resin to the natural rubber. Then the mechanicalproperties of three types of composite material using natural rubber vulcanized,unvulcanized and reinforced rubber have been investigated . Each type was coatedwith six percentages of epoxy resin (0% , 20% , 40%, 60%, 80%, and 100 %) . Thevalues of Young’s modulus, yield stress, tensile strength and yield strain whichwere calculated for each case and for all percentages of epoxy resin. It is concludedthat the properties of the new composite material using natural rubber ismuchbetter than the properties of the pure natural rubber and the increasing in thepercentage of epoxy resin in vulcanized rubber leads to a decrease in Young’smodulus and increasing percentage of epoxy resin in unvulcanized rubber andreinforced rubber leads to an increase in Young modulus